Methodological aspects for the study of nucleation and growth mechanisms of metals from deep eutectic solvents based on choline chloride - Thao, Dao Vu Phuong; Lanh, Pham Thi; Xuan, Chu Thi; Hieu, Nguyen Van; Tu, Le Manh (Vietnam Journal of Science and Technology, 2022)
This paper presents a methodology for studying nucleation and growth mechanisms of metals onto a glassy carbon electrode in a deep eutectic solvent (DES), a mixture of choline chloride and urea at a molar ratio of 1:2. Characteristics and composition of Co(II) complexes formed with the DES were evaluated by means of UV-vis measurements, which confirmed the good stability of these species at room temperature. To elucidate the methodology, kinetic and mechanistic aspects of the early stage of cobalt electrodeposition were studied using cyclic voltammetry and chronoamperometry onto glassy carbon electrode from the DES. From the voltammetric study, typical reduction and oxidation stages were identified. From the behavior of experimental current density transients, it was found that the Co electrodeposition could be described by a model comprising Co three-dimensional nucleation and diffusion-controlled growth taking into account the induction – time. The diffusion coefficient of cobalt ions in DES was determined by two methods: cyclic voltammetry and kinetic parameters obtained from model fitting. Moreover, the dimensionless analyses of the experimental current density transients have shown the dominance of progressive nucleation type during the electrodeposition of cobalt. Characterization techniques such as scanning electron microscopy, energy-dispersive X-ray spectroscopy, and elements mapping were used to verify the presence and the nucleation type of cobalt onto the glassy carbon electrode surface, showing a good agreement with the prediction made from the proposed model. This also corroborates the feasibility of the proposed methodology for studying the electronucleation of metals.